Dampak Keputusan Investasi, Kinerja Keuntungan dan Komposisi Modal Terhadap Pencapaian Nilai Entitas Ritel (Sektor Supermarket dan Convenience Store) Yang Terdaftar di BEI Periode 2011-2022 - Bhikuning, Dixian; Wasiati, Hera; Rahmadani, Anggita Novita (LPPM Institut Pendidikan Nusantara Global, 2024)
This quantitative study seeks to assess the impact of Investment Decisions (PER), Profitability (ROE), and Capital Composition (DER) on the Company Value (PBV) of five retail companies in the supermarket and convenience store industry Included in the Indonesia Stock Exchange's listings from 2011 onward 2022. Classic assumption tests, multiple linear regression analysis, correlation coefficients, determination coefficients, t-tests, and F-tests were employed to analyze the data. The results of the t-test reveal that there is no connection between profitability and the valuation of retail companies, at a significance level of 0.318 or higher. Another t-test demonstrates a significance level of 0.00, which is less than 0.05. This suggests that investment decisions and capital composition have an impact on the valuation of retail companies in the supermarket and convenience store industry. Conversely, the outcomes of the F-test, achieved at a significance level of 0.00, are below 0.05, indicate that profitability, investment decisions, and capital composition collectively impact the value of retail companies in the supermarket and convenience store industry.